2020
DOI: 10.1136/bmjopen-2020-040753
|View full text |Cite
|
Sign up to set email alerts
|

Activities outside of the care setting for people with dementia: a systematic review

Abstract: ObjectivesTo summarise the evidence from interventions investigating the effects of out of care setting activities on people with dementia living in residential aged care.DesignA systematic review.MethodsA systematic search of electronic databases (PubMed, PsycINFO, Scopus, Web of Science and the Cochrane Library) was performed to identify intervention trials published from journal inception to January 2020. Controlled trials, or quasi-experimental trials, which measured pre-intervention, post-intervention or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…For people living in residential aged care, including the large proportion living with dementia, there is a need for suitable interventions that offer opportunities for engagement in activities that are personally meaningful and promote cognitive stimulation, physical activity and social connection ( D'Cunha et al, 2020 ; O’Rourke et al, 2018 ; Tierney & Beattie, 2020 ). An increase in social isolation and restrictions in physical activity may increase neuropsychiatric symptoms, feelings of loneliness, poorer quality of life and cognitive function for older people with dementia living at home but particularly for older people living in residential aged care ( Curelaru et al, 2021 ; Lion et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…For people living in residential aged care, including the large proportion living with dementia, there is a need for suitable interventions that offer opportunities for engagement in activities that are personally meaningful and promote cognitive stimulation, physical activity and social connection ( D'Cunha et al, 2020 ; O’Rourke et al, 2018 ; Tierney & Beattie, 2020 ). An increase in social isolation and restrictions in physical activity may increase neuropsychiatric symptoms, feelings of loneliness, poorer quality of life and cognitive function for older people with dementia living at home but particularly for older people living in residential aged care ( Curelaru et al, 2021 ; Lion et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, art galleries and museums around the world have developed access programs to provide art activities for people with dementia. Often developed in partnership with health, dementia support or aged care services, these access programs have the potential to enhance the psychosocial and psychophysiological wellbeing of people with dementia, providing an opportunity for intellectual stimulation, creative engagement, social interaction, and personal reflection (Camic et al, 2016; Cavalcanti Barroso et al, 2022; D'Cunha et al, 2020; Ullán et al, 2013). A taxonomy of arts interventions for people with dementia listed eight principles and features: transformation, possibility, connection, expression, involvement, selfhood, humanity, and engagement (Cousins et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is not a widely accepted definition, participation in leisure activities can be defined as the use of relaxing, interesting, and enjoyable activities spent outside of work that fosters well-being and life satisfaction [ 3 ]. Research on this topic has shown a positive correlation between positive health-related outcomes and different aspects of leisure activities such as playing sports, games, and cards; visiting friends; making excursions; and taking trips [ 1 , 2 , 4 , 8 ]. Within this broad framework, the concept of participation in leisure activities is one of the most critical issues among the elderly population and goes with the concept of “successful aging” [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%